Report of the 41st annual conference held in The Central Hall, Westminster, May 25th to 28th, 1942. - Labour Party (London : Labour Party, 1942)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Wereldoorlog 2; Groot-Brittannië.